Narrative Patterns in Indonesian Fine Art - Acep Iwan Saidi; Dyah Gayatri Puspitasari; Ferry Fauzi Hermawan (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
This paper aims to describe the structure and pattern of narratives in art, which in this case Indonesian fine art is used as a case study. This topic is important considering that the assumption that works of fine art have narrative characteristics has become common knowledge, but the structure and narrative patterns within the genre of work of fine art that can be used as a reference have not yet been formulated. By using a structural semiotic approach, studies in this paper have found that narrative patterns in fine art are a combination of denotative visual sign units presented as works on the syntagmatic axis of language (visual) interrelated to form associations or groups of narrative connotations on the paradigmatic axis (community knowledge system). This proposition, as well as several other formulations found in the analysis, has a significant contribution to the development of fine art, both theoretically and practically, both in Indonesia and the world.